2020
DOI: 10.1017/jfm.2020.639
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of streamwise wall-shear stress fluctuations in turbulent channel flows

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 105 publications
3
15
0
Order By: Relevance
“…As quantifies , which features the same sign as , this observation is consistent with the work of Cheng et al. (2020), which showed that the footprints of the inactive part of attached eddies populating the logarithmic region are actively connected with large-scale negative . Other values yield similar results and are not shown here for brevity.…”
Section: Resultssupporting
confidence: 91%
“…As quantifies , which features the same sign as , this observation is consistent with the work of Cheng et al. (2020), which showed that the footprints of the inactive part of attached eddies populating the logarithmic region are actively connected with large-scale negative . Other values yield similar results and are not shown here for brevity.…”
Section: Resultssupporting
confidence: 91%
“…Percolation analysis has been successfully used not only for identifying vortex clusters in turbulent channel flows (del Álamo et al 2006) but also for detecting three-dimensional velocity structures (Sillero 2014;Hwang & Sung 2018) and quadrant events in turbulent channels (Lozano-Durán, Flores & Jiménez 2012) and homogeneous shear turbulence (Dong et al 2017) based on a three-dimensional extension of the classical quadrant analysis (Wallace et al 1972;Willmarth & Lu 1972). More recently, the percolation analysis for threshold selection has also been employed by Cheng et al (2020a) for the identification of scale-based structures of streamwise wall shear stress fluctuations in turbulent channel flows.…”
Section: Identification Methodsmentioning
confidence: 99%
“…They provided evidence that the large-scale motions near the wall scale in inner units, and Cheng et al. (2020) revealed that the footprints of the large-scale motions manifest as large-scale regions of negative wall friction.…”
Section: Introductionmentioning
confidence: 99%